PENGARUH FAKTOR KEUANGAN, NON KEUANGAN TERHADAP PERINGKAT OBLIGASI: MANAJEMEN LABA SEBAGAI INTERVENING - Partiningsih, Dewi Noor; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to analyze the influence of financial and non financial factor to the bond ratingwith earnings management as the intervening variable. The population is the annual report of all non financialbond rating issuance companies which are listed in IDX in 2009-2013 periods. The samples have been selectedby using purposive sampling and 12 companies have been obtained. The data analysis technique has been doneby using multiple regressions and path analysis in the form of sobel test. The result of partial test on 10%significance level shows that liquidity has significant influence to the earnings management whereasprofitability and auditor reputation does not have any significant influence to the earnings management.Auditor reputation and liquidity has significant influence to the bond rating whereas profitability and earningsmanagement does not have any significant influence to the bond rating. The hypothesis test has been done byusing sobel test on 10% significance level shows that liquidity has an influence to the earnings management andliquidity has an influence to the bond rating but earnings management cannot mediate the correlation betweenliquidity and bond rating indirectly.Keywords: Bond Rating, Profitability, Liquidity, Auditor Reputation, Earnings Management